Nuclear North Korea a debate on engagement strategies - Cha, Victor D., d 1961; Kang, David C. q (David Chan-oong) 1965 (Contemporary Asia in the world, 2018)
"Fifteen years after its initial publication, Nuclear North Korea is still as relevant as ever. Coming to the issues from different perspectives--Kang believes the threat posed by Pyongyang has been inflated and endorses a more open approach, while Cha is more skeptical and advocates harsher measures--the authors together present clear-eyed reflection and authoritative analysis. They refute a number of misconceptions and challenge much faulty thinking that surrounds the discussion of North Korea, particularly the idea that North Korea is an irrational nation. Cha and Kang contend that however provocative, even deplorable, the Pyongyang government's behavior may at times be, it is not incomprehensible or incoherent. In an intelligent and trenchant debate, the authors explore the inherent logic of North Korean politics, look at the implications of a nuclear North Korea for East Asia and U.S. homeland security, and rigorously assess historical and current U.S. policy, and provide a workable framework for constructive policy that should be followed by the United States, Japan, and South Korea if engagement fails to stop North Korean nuclear proliferation. With a new chapter on the way forward for the international community in light of continued nuclear tensions with North Korea, this book remains an essential resource to understanding the state of affairs on the Korean peninsula."--Provided by publisher